Public support for cancer prevention, screening, treatment and care policies in Aotearoa New Zealand: a synthesis of evidence from a national survey - Bronwen McNoe; Rana Peniamina; Richard Edwards; Rose Crossin; Andrew Gray; Ella Iosua; Jerram Bateman; Shane Bradbrook; Jeannine Stairmand; Virginia Signal; Louise Signal (New Zealand Medical Journal, 2026)
aim: We aimed to synthesise evidence on public support for cancer prevention, screening, treatment and care policies across the cancer continuum in Aotearoa New Zealand, and to consider implications for policy and governance. methods: This viewpoint article draws together findings from a co-ordinated programme of national survey research comprising one shared methods paper and seven topic-specific reports examining public support for population-level prevention policies and cancer health services. results: Across all topic areas, public support for the evidence-based cancer-related policies presented was consistently high. Strong majority support was evident for prevention, vaccination, screening, treatment and care, with broadly consistent patterns across political parties in many cases. Support was strong for population-level prevention measures targeting tobacco and vaping, unhealthy food and sugary drinks, alcohol, ultraviolet radiation exposure and vaccine-preventable infection. There was also substantial public endorsement of restrictions on industry lobbying and commercial influence over health policymaking. Strong support was observed for timely diagnosis, accessible treatment and sustainable health system funding, including a willingness to contribute through taxation when revenues are transparently earmarked. conclusion: These findings demonstrate a clear public mandate for evidence-based cancer policy across cancer prevention, screening, treatment and care in Aotearoa New Zealand. Barriers to action appear political rather than societal, underscoring the need for decisive political leadership consistent with Te Tiriti o Waitangi and public expectations.